Elastic routing for survivable networks. (2015) - Shinko, Ilir; Fouquet, Yoann; Nace, Dritan
In this paper, we report a study on survivable networks and a new restoration method called Elastic Robust Routing (ERR). This method can be seen as a variant of Shared Robust Rerouting (ShRR), while both methods rely on some well-known existing rerouting strategies. The ERR strategy derives quite naturally from the protection techniques and the ShRR strategy. In contrast to ShRR, in ERR new rerouting paths are not allowed to be established during the recovery process; only the nominal routing paths are allowed to be 'widened' to fit the traffic demand to available capacity. The term elastic refers to the use of nominal paths whose bandwidths vary according to the state of the network. This way, the ERR strategy uses the same pool of paths for both routing and rerouting. In the literature, very few works focus on the related distributed issues of rerouting strategies. We discuss this issue for both methods and emphasise the related network management.